Solar Energy Assisted Heat Pump Water Heater (Universitas Darul Ulum, 2025)
A solar energy-assisted heat pump water heating system has been developed to improve household water heating efficiency. The system consists of a compressor, evaporator, capillary pipe, and condenser wrapped around a tank to avoid leakage. This study aims to evaluate the performance of the system through coefficient of performance (COP) measurements at 30 liter and 60 liter tank capacities. The test was conducted for five days with sunny weather conditions and data collection on temperature, solar radiation, and compressor power between 10:00 am and 2:00 pm. The results showed that the highest COP of 2.46 was obtained at a capacity of 60 liters, while 1.25 for a capacity of 30 liters. An increase in the final water temperature led to a decrease in COP, indicating that the system is more efficient at lower temperatures. This system shows the potential of utilizing renewable energy for efficient and economical water heating for household applications.